2015
DOI: 10.1080/1475939x.2015.1030441
|View full text |Cite
|
Sign up to set email alerts
|

Utilising social networking sites to improve writing: a case study with Chinese students in Malaysia

Abstract: With the advancement of technology, writing in English is no longer confined to the classroom as nowadays students are exposed to various forms of writing on the Internet. Specifically with Generation Y in mind, online writing is a new method that needs to be implemented to enhance Malaysian students' writing skills. This article aims at identifying what motivates English as a Second Language students to write in English on Facebook. Ten Chinese-speaking students from a private urban school were selected for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Although no significant improvements regarding lexical richness and grammatical accuracy were present, Japanese EFL learners in the experimental group were found to make meaningful progress on each assessment test in terms of writing fluency while there was no significant improvements in the control group. This finding conforms to the research conducted by Vikneswaran and Krish (2016), who found that Facebook promoted writing fluency of Chinese ESL students largely thanks to the contributions and discussions of ideas on the private group page.…”
Section: Theme 1: Practicing Multiple Language Areas and Literaciessupporting
confidence: 91%
“…Although no significant improvements regarding lexical richness and grammatical accuracy were present, Japanese EFL learners in the experimental group were found to make meaningful progress on each assessment test in terms of writing fluency while there was no significant improvements in the control group. This finding conforms to the research conducted by Vikneswaran and Krish (2016), who found that Facebook promoted writing fluency of Chinese ESL students largely thanks to the contributions and discussions of ideas on the private group page.…”
Section: Theme 1: Practicing Multiple Language Areas and Literaciessupporting
confidence: 91%
“…This connection especially applied to the study of foreign languages, where students felt more comfortable in writing and participating in online discussions. Burdens of grammar, spelling and vocabulary would be eased, as students felt they were not judged and could learn from their mistakes (Vikneswaran & Krish, ).…”
Section: Informal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 99%
“…On the other hand, the researchers mentioned in their studies (Evans, 2014;Lee et al, 2016;Menkhoff et al, 2015;Suthiwartnarueput & Wasanasomsithi, 2012;Van den beemt et al, 2019;Vikneswaran & Krish, 2016) that there are effects in influencing social media. This current study is existing research repeatedly focused on one aspect: social media in general in all the subjects' science and math.…”
Section: Discussionmentioning
confidence: 99%
“…A significant consequence is the use of social media, and Facebook in particular, to write lessons and language courses. Studies based on writing and language have shown increased student outcomes and engagement by using social media as learning resources (Lee, Koo, & Kim, 2016;Suthiwartnarueput & Wasanasomsithi, 2012;Van den beemt et al, 2019;Vikneswaran & Krish, 2016).…”
Section: Introductionmentioning
confidence: 99%